1997
DOI: 10.1063/1.365220
|View full text |Cite
|
Sign up to set email alerts
|

Si 1−x−y Ge x C y alloy band structures by linear combination of atomic orbitals

Abstract: We have applied a virtual crystal approximation to the linear combination of atomic orbitals method to calculate critical point energies of unstrained Si1−x−yGexCy alloys spanning the composition parameter space. Additionally, we have calculated the band structure across the Brillouin zone for a series of alloy compositions. We found the band energies had significant bowing departures from linearity throughout the system. In some cases, the energy band gap was not monotonically dependent on composition. Our th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Previously, the LDA-pseudopotential calculations 6 reported GeC to be indirect gap (⌫ -X) alloy. Similarly, calculations 21 using the virtual crystal approximation found the minimum gap to be indirect for Ge 0.62 C 0.38 . In Table II, we have also reported our results for SiC for which the calculated results are in agreement with previous calculations and experiment in predicting SiC to be an indirect gap (⌫ -X) material.…”
Section: B Electronic Propertiesmentioning
confidence: 87%
“…Previously, the LDA-pseudopotential calculations 6 reported GeC to be indirect gap (⌫ -X) alloy. Similarly, calculations 21 using the virtual crystal approximation found the minimum gap to be indirect for Ge 0.62 C 0.38 . In Table II, we have also reported our results for SiC for which the calculated results are in agreement with previous calculations and experiment in predicting SiC to be an indirect gap (⌫ -X) material.…”
Section: B Electronic Propertiesmentioning
confidence: 87%
“…The tightbinding atomic basis set consists of one s orbital, three p orbitals, and one excited s* orbital per atom. We propose a lattice disorder parameter ⌬V S * P to reproduce the observed initial reduction of band gap of strained Si 1Ϫx C x , while previous LCAO calculactions 18 showed no such effect.…”
Section: Introductionmentioning
confidence: 86%
“…Note that this VCA does not include the local strain as reported in Ref. 18. The band gap shrinkage is due to the local strain around the substitutional C atoms, which are randomly distributed in the Si 1Ϫx C x alloys.…”
Section: A Modified Lcao Calculation Of Si 1àx C X Alloymentioning
confidence: 99%
“…Therefore, process margin for SiGe HBT fabrication can be relaxed. On the other hand, it has been reported that the bandgap and the band offsets with respect to the conduction band and valence band sensitively varies with C contents and strain in Si 1ÀxÀy Ge x C y films [151][152][153][154][155][156][157][158][159][160][161]. On the basis of the control over the band alignment in the Si 1ÀxÀy Ge x C y hetero structures, Si 1ÀxÀy Ge x C y epitaxial films were applied to channel layers in MOSFET [162,163], high-electron mobility transistor (HEMT), and optical devices [164][165][166].…”
Section: Formation Of Sigec Alloysmentioning
confidence: 97%